The understanding of food fraud among consumers in Klang Valley, Malaysia - Ahmad, Nur Nisaa; Khairatun, Siti Nurhayati (Goodwood Publishing, 2020)
Purpose: This study aimed to understand food fraud awareness and understanding from the Malaysian consumers' perspective. Research methodology: Five face-to-face in-depth interviews using random purposive sampling were administered to obtain insights into Malaysian consumers' multiple realities. A peer review with an expert in quality control of the food supply chain was done to increase data trustworthiness and validate the findings. Results: The findings indicated that awareness about food fraud among Malaysian consumers is relatively low. As consumers do not have the ability and necessary tools to evaluate food fraud, regulatory authority, certification bodies, and trade associations are responsible for protecting food integrity by mitigating food fraud. Limitations: The study was self-funded and conducted in Klang Valley, Malaysia. Due to that, no generalization can be made from the data. Contribution: This outcome can be used as a knowledge base for policymakers and trade industries in regulating the sustainability and integrity of the food industry, particularly for consumer outreach programs in disseminating accurate technical knowledge of food to the public. Keywords: Food industry, Food inspection, Consumers education, Consumer protection, Consumer awareness, Food consumption